Análise dos mecanorreceptores e terminações nervosas livres do ligamento meniscotibial medial do joelho com imunofluorescência e microscopia confocal - Alencar Neto, Jonatas Brito de (2022)
The meniscotibial ligaments, also known as the coronary ligaments, are a fibrous band that peripherally connects the menisci to the tibia. Currently, as meniscus ramp deficiency, they have been associated with concomitant injury to the meniscotibial ligaments, being causes of instability in ACL-deficient patients. The study of this structure is essential to define its main characteristics and understand its best functioning, so that we can treat it according to the same cases of rupture. Male knee ligaments were obtained during organ donation sent from 20 deceased organ donors effected by the Intra-Hospital Commission for Organ and Tissue Donation for Transplantation (CIHDOTT) after brain death, all adults. The ligaments were medium, fast and cut. Sections of 1 were prepared with hematomas on stained slides (HE), to study 8 μm scientific research lessons, and sections of 5 sessions of immunofluorescence with protein gene product (PGP), followed by microscopic analysis (Zeiss. LMS 710). The medial LMT was identified in 100% of dissections, exhibiting a mean width of 32,25 ± 3,09 mm, mean length of 7,07 ± 1,34 mm, mean thickness of 3,53 ± 0,27 mm and average weight of 0,6728 ± 0,1346g. Histological sections in HE showed dense and well-organized collagen fibers, in addition to the presence of vascular tissue. In all receptors projected in parallel, type I (Ruffini-like) and type IV (nerve endings to parallel fibers) mechanoreceptors were identified, ranging from parallel fibers to coiled fibers. There were also several formats, with nerve endings and irregular. neural elements were all most close to the tibial insertion of the medial LMT. Thus, it was concluded that the LMT is a distinct ligament structure in the posteromedial aspect of the knee and presents a peripheral nervous structure, primarily type I and IV mechanoreceptors. Such findings lead us to believe that the medial LMT presents proprioception and anterior and posteromedial stabilization of the knee.